1999
DOI: 10.1111/j.1540-8167.1999.tb00260.x
|View full text |Cite
|
Sign up to set email alerts
|

The Valve of Vieussens: An Important Cause of Difficulty in Advancing Catheters into the Cardiac Veins

Abstract: The valve of Vieussens is a frequent cause of obstruction to passage of a catheter in postmortem and in vivo studies. An acute bend in the vein, with or without lodgment in a tributary, is the other common cause. In adults, venous luminal diameter is not a cause of obstruction to the passage of a 7-French catheter in the coronary sinus or proximal GCV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
34
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(36 citation statements)
references
References 2 publications
1
34
1
Order By: Relevance
“…These procedures are well known for their potential technical difficulties. Coronary sinus cannulation by conventional deflectable 7-F catheter has been reported by Corcoran et al to have been obstructed by the Vieussens valve in 46% of the cases [14]. Our results could not support these findings having shown a well-developed Vieussens valve in only 15% of cases.…”
Section: Coronary Sinus Interventioncontrasting
confidence: 44%
See 1 more Smart Citation
“…These procedures are well known for their potential technical difficulties. Coronary sinus cannulation by conventional deflectable 7-F catheter has been reported by Corcoran et al to have been obstructed by the Vieussens valve in 46% of the cases [14]. Our results could not support these findings having shown a well-developed Vieussens valve in only 15% of cases.…”
Section: Coronary Sinus Interventioncontrasting
confidence: 44%
“…Although variable prevalence of the Vieussens valve has been published, in 57%, 59% and 65% of cases [1,16,17], in none of these reports has an incidence as high as 46% for the presence of a developed valve been documented. Another explanation of the technical difficulty for coronary sinus cannulation is the possible flexing of the great cardiac vein [14]. Our results may provide anatomical basis for such a suggestion.…”
Section: Coronary Sinus Interventionmentioning
confidence: 65%
“…At this site, the valve of Vieussens is often present, which is an important cause of problems advancing the catheter into cardiac veins (8). In the current study, the vein of Marshall was observed in only 13 patients (34%).…”
mentioning
confidence: 51%
“…There are frequently valves of Vieussens at this location. These valves may pose difficulty in directing and passing the catheter into the cardiac veins (28). It is hard to visualize the vein of Marshall compared to other veins in CT studies, requiring special care and thorough examination.…”
Section: Discussionmentioning
confidence: 99%